Analyzing Dominant Cultural Narratives of Religious Pluralism: A Study of Oprah.com - Patricia Webb; Zach Waggoner (Journal of the Assembly for Expanded Perspectives on Learning, 2004)
This essay analyzes Oprah.com, the website for multimedia mogul Oprah Winfrey, to examine the tensions between dominate religious ideologies and pluralism in America.